Method of back-oblique sounding of the ionosphere in HF-range for operational compensation of measurement errors of early-warning radars - Chirov, Denis S. (2018 Systems of Signals Generating and Processing in the Field of on Board Communications, 2018)
At present, there are a fairly large number of methods of ionospheric measurements, which use radio waves: radiosonde, partial reflection method, coherent and incoherent scattering of radio waves methods, various phase methods (dispersion interferometry, Doppler measurements) and etc. Modern methods of radiosonde, carried out from one point, includes four types of radiosonde: vertical - ground, oblique, external and transionospheric. Back-oblique sounding can also be included here, which can be implemented by the same radiophysical complex. From the point of view of compensation of measurement errors of early-warning radars, the oblique and back-oblique sounding methods are optimal, because these methods make it possible to obtain operative estimates of the ionosphere state in a given direction (including at low elevation angles). One of the most promising methods back-oblique sounding of the ionosphere is the method of estimating the electronic concentration in the ionosphere according to scattered by the ionosphere signal. The aim of the article is to assess the possibility of application the method of estimating the electronic concentration in the ionosphere according to scattered by the ionosphere signal for quickly compensate of measurement errors of radiolocation early-warning station. The signal reflected by the ionosphere consists of a mirror-reflected component and a component caused the scattering. The parameters of the scattered signal component depend on the type of single ionospheric irregularities. The results of numerical modeling of the process of the reflection of the HF signal from the ionosphere show that there is the possibility of detecting the scattered by ionosphere heterogeneity of the components of the sounding signal at the point of ionoprobe placement at a high sensitivity of the receiver. Such an approach will significantly improve the efficiency of measuring the ionosphere parameters in a given direction.